DIMENSI METRIK DAN DIAMETER DARI GRAF ULAT Cm,n - Restu Ria Wantika (Universitas PGRI Adi Buana Surabaya, 2016)
Graf is a pair (V,E) where V set of vertices is not empty and E set side. Let u and v are the vertices in a connected graph G, then the distance d (u, v) is the length of the shortest path between u and v in G. The diameter of graph G is the maximum distance of d (u, v) .For the set of ordered of vertices in a connected graph G and vertex , the representation of v to W is . If r (vÃ¢â€â€šW) for each node v∈V (G) are different, then W is called the set of variants from G and the minimum cardinality of the set differentiator is referred to as the metric dimensions. Based on the characteristics of the vertices and sides of the graph have many types of them are caterpillars and graph graph fireworks, which both have in common at the center of the graph shaped trajectory and earring star-shaped graph. In this paper will prove that Graf caterpillar with has diameter and metric dimensions . Keywords: dimensional graph, graph diameter, star graph, graph caterpillar ..